PENGARUH NAUNGAN TAJUK KELAPA SAWIT TERHADAP SUHU DAN KELEMBAPAN TANAH DI KEBUN PRAKTIK ITSI - Fuady Nur Akbar; Tiaini Siregar; Roma Uli Nababan; M. Yudha Prawira; Alvin Romadhoni Nasution; Fathir Albani (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
Soil microclimate is an environmental factor that influences to growth of oil palm plantations, particularly soil temperature and soil moisture. This study aimed to analyze the effect of canopy cover levels on soil microclimate conditions in oil palm plantations area. The method use was filed observation with a comparative approach on three canopy categories, namely dense, moderate, and open canopies. Soil temperature and soil moisture were measured directly at several observation times using a soil thermometer and a soil moisture meter. The data were analyzed descriptively and comparatively to identify difference in soil microclimate conditions under different canopy cover levels. The results showed that open canopies tended to have higher soil temperatures, while dense canopies were able to maintain soil moisture and temperature stability. Difference in canopy cover levels influenced soil microclimate conditions in oil palm plantations areas.